Long-Term Use of Aldosterone-Receptor Antagonists in Uncontrolled Hypertension: A Retrospective Analysis. (20th February 2011) - Jansen, Pieter M.; Verdonk, Koen; Imholz, Ben P.; Jan Danser, A. H.; van den Meiracker, Anton H.
Abstract : Background . The long-term efficacy of aldosterone-receptor antagonists (ARAs) as add-on treatment in uncontrolled hypertension has not yet been reported. Methods . Data from 123 patients (21 with primary aldosteronism, 102 with essential hypertension) with difficult-to-treat hypertension who received an ARA between May 2005 and September 2009 were analyzed retrospectively for their blood pressure (BP) and biochemical response at first followup after start with ARA and the last follow-up available. Results . Systolic BP decreased by22 ± 20 and diastolic BP by9.4 ± 12 mmHg after a median treatment duration of 25 months. In patients that received treatment >5 years, SBP was33 ± 20 and DBP was 16 ± 13 mmHg lower than at baseline. Multivariate analysis revealed that baseline BP and follow-up duration were positively correlated with BP response. Conclusion . Add-on ARA treatment in difficult-to-treat hypertension results in a profound and sustained BP reduction.